Training on Improving Entrepreneurial Skills for Students of the Faculty of Economics and Business, Malikussaleh University - Jannah, Miftahul; agustinar; Rianti. S, Nova; Agustinawati; Ramazalena, Rauzi; Habibi, Muhammad; Syahyudi, Ilham (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2024)
Abstract: The "Entrepreneurial Skill Enhancement Training" for students of the Faculty of Economics and Business at Malikussaleh University aims to equip students with practical skills and relevant knowledge in the field of entrepreneurship. In the rapidly changing era of globalization and digitalization, entrepreneurial skills have become crucial for enhancing individual competitiveness and driving economic growth. This program consists of a series of interactive workshops, seminars, and case studies covering topics such as business planning, digital marketing, financial management, and product and service innovation. Active participation from industry practitioners as speakers provides real insights into the challenges and opportunities present in the market. Through a hands-on learning approach, it is expected that students will not only understand entrepreneurial theory but also apply it in real-world contexts. Evaluation is conducted using pre-test and post-test methods to measure changes in participants' knowledge and skills. The outcomes of this training are expected to encourage students to be more proactive in creating business opportunities, thus positively contributing to the local economy and strengthening the entrepreneurial ecosystem in the region.